Religion and Development: An Exploration of the Basis of Wholistic Education in Universal Basic Education Programme in Nigeria - Kwaji Tizhe Takwate (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
Universal Basic Education (UBE) programme in Nigeria was launched in 1999, with the goal of providing “free, universal and compulsory basic education for every Nigerian child aged 6-15 years”. The scope of UBE among others include the initiation for the acquisition of functional literacy, numeracy and life skill for adults and special programmes of encouragement to all marginalized groups (girls, women, nomads, out-of-school youth and Quranic students). Religion has been destructively criticized largely due to the sufferings and devastating situations humanity has and is passing through over the years in Nigeria and based on these, religion is seen as being pervasive and it continues to weaken the moral fiber of UBE programme implementation. Therefore, any developmental tool that is effective and can drive home development must be such that is particularly viable in tackling the problems of religion. Thus, in a bid to revitalize a society already bedeviled with various degenerating ills, religious education which is wholistic in nature should become everyone’s focus. This paper described the importance, the curriculum and technique for teaching wholistic religion education for religious tolerance and sustainable development in UBE. The paper concluded that no known religion is devoid of moral and ethical principles and religion is a force which has mostly influenced the character of mankind. This paper maintained that development can be enriched by the insights offered by religion, faith, spirituality and values. Based on these, the paper recommended that religion should be carried along in making policies, the study of moral education should be made compulsory in all categories of learning and the National Orientation Agency should also include it in their plans and school curriculum should be more of reflective thinking.